Pengaruh Penggunaan Metode Eksperimen dalam Mendukung Kemampuan Kognitif Anak Usia Dini: Studi di SPS Bambim As-Shafa Tasikmalaya - Zulianti, Sindi (AS-SABIQUN, 2024)
The purpose of this research is to conduct science experiments on floating, sinking and floating objects in liquid to support cognitive abilities in early childhood. By providing opportunities to experience and learn directly can develop a deeper understanding between theory and practice, opening space for creativity and problem solving. This research uses descriptive qualitative method, conducted at SPS Bambim As-Shafa Tasikmalaya. The data collection techniques used were the results of observation and documentation, then the collected data were analyzed by data reduction, data presentation and conclusion drawing. The results of the study showed that children were very enthusiastic and paid direct attention to the changes that occurred in the science experiments carried out. The materials used include tools and materials that are safe and simple and easily recognized by children in their environment. Experiments of floating, sinking and floating objects are science learning that can directly support children's cognitive abilities, triggering children to train their five senses, find and understand events from the symptoms of the objects tested